Peran Kepemimpinan Guru PAK dalam Meningkatkan Motivasi Belajar Peserta Didik di SDN Ebang (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study aims to explain the contribution of Catholic Religious Education (PAK) teacher leadership in improving students' enthusiasm for learning at SDN Ebang. The problem underlying this study is the weak motivation of students to learn as indicated by low participation, lack of enthusiasm, and minimal involvement in the teaching and learning process. The method used in this study is a qualitative approach with descriptions, which includes data collection techniques such as observation, structured interviews, and document collection. The subjects of the study consisted of a PAK teacher, the principal, and two students from grades V and VI who were selected by considering the principle of data satisfaction. The findings of this study indicate that PAK teachers function significantly as mentors, role models, spiritual directors, innovators, driving learning communities, and assessors. These roles have a positive influence on increasing students' learning motivation in the cognitive, affective, and spiritual aspects. The uniqueness of this study lies in the combination of various aspects of PAK teacher leadership in a public elementary school environment as well as an examination of internal and external factors that influence learning motivation in the digital era. This study concludes that flexible and contextual PAK teacher leadership has a crucial role in building comprehensive learning motivation amidst limited facilities and student diversity.